Optimization of the chemical mechanical polishing process for optical silicon substrates - Zhong, Z. W. (2013)
Chemical mechanical polishing (CMP) experiments are performed to study the effects of four key process factors on the flatness and surface finish of the polished optical silicon substrates and on the material removal rate (MRR). The experimental results and analyses reveal that the pad rotational speed and polish pressure have significant effects on the MRR, the interaction of the polish head rotational speed and slurry supply velocity and the interaction of the polish pressure and polish head rotational speed have significant effects on the flatness, and the pad rotational speed has a significant effect on the surface roughness R t of the optical silicon substrates polished. The optimal combination of the four factors investigated is a polish pressure of 9,800 Pa, a pad rotational speed of 20 rpm, a polish head rotational speed of 20 rpm, and a slurry supply velocity of 100 ml/min. A confirmation CMP experiment has been carried out using the optimal process parameter setting obtained from the design of experiments analyses. The goal to attain optical silicon substrates with nanometric surface roughness and micrometric flatness by an optimized CMP process with a high MRR simultaneously so as to reduce the polishing time to only 15 min from over 8 h has been achieved.